2(4-2x)-5=-2x(x+5)+8x

Simple and best practice solution for 2(4-2x)-5=-2x(x+5)+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4-2x)-5=-2x(x+5)+8x equation:



2(4-2x)-5=-2x(x+5)+8x
We move all terms to the left:
2(4-2x)-5-(-2x(x+5)+8x)=0
We add all the numbers together, and all the variables
2(-2x+4)-(-2x(x+5)+8x)-5=0
We multiply parentheses
-4x-(-2x(x+5)+8x)+8-5=0
We calculate terms in parentheses: -(-2x(x+5)+8x), so:
-2x(x+5)+8x
We add all the numbers together, and all the variables
8x-2x(x+5)
We multiply parentheses
-2x^2+8x-10x
We add all the numbers together, and all the variables
-2x^2-2x
Back to the equation:
-(-2x^2-2x)
We add all the numbers together, and all the variables
-(-2x^2-2x)-4x+3=0
We get rid of parentheses
2x^2+2x-4x+3=0
We add all the numbers together, and all the variables
2x^2-2x+3=0
a = 2; b = -2; c = +3;
Δ = b2-4ac
Δ = -22-4·2·3
Δ = -20
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 10x+4=6x12 | | 4(c+12=2c | | -2=-2s-5 | | F(9)=2x-3 | | x+5=5x=25 | | -1/2(6-4x)+2x=-16 | | 2x+3(5x-7)=487 | | 9(u+4)=63 | | (3x-5)+(4x+7)=180 | | 12x+8x+3+x= | | 7(5-5x)=210 | | .5x+8=3x−3 | | -1(6n)=-14 | | −5x​ =4 | | -7(5-5x)=210 | | 7x+8=1x+9 | | (3x-18+2(-3X+4)=-13 | | 3(4x+1)-4x=3=-18 | | 3/5=172/5÷h | | d-15=-12 | | -6x+14=128x | | 8+16a=7a-28 | | n+8(n+20)=110+4n | | 14x-168=4x+74 | | b/11=12 | | 28=x+348/19 | | 2x+10=-2(x+9) | | 7×-4=3+8x | | 14x+3=6x+51 | | 12m=-12 | | 7y-20=5y+10 | | -39=6(1+3m)-(8m-5) |

Equations solver categories